ANALISIS KEBIJAKAN PRIVASI DAN TANGGUNG JAWAB PLATFORM DIGITAL DALAM MENCEGAH PHISHING - Ibnu Fahmi; Muhammad Azka; Asmak Ul Hosnah (Journal of Innovative and Creativity, 2026)
Phishing attacks, which result in significant losses for digital platform users, are one of the most common types of cybercrime. This study examines how privacy policies and digital platforms' responsibilities in preventing phishing in Indonesia relate to each other. A juridical-normative approach was used in the research. This included examining relevant regulations such as the Electronic Information and Transactions Law (UU ITE) and regulations concerning Personal Data Protection, as well as evaluating how privacy policies are implemented on various digital platforms. The results indicate that, despite existing laws governing the security and protection of personal data, most platforms still do not implement the best protection standards. Factors that increase the likelihood of phishing include unclear data management, inadequate user instructions, and poor threat verification and warning systems. Furthermore, threat management is often ineffective because it is unclear how platforms, users, and electronic system operators are held accountable. This study suggests that strengthened regulations, higher security standards, and cross-sectoral collaboration are crucial to reducing losses caused by phishing. These findings are expected to form the basis for developing a better data protection and cybersecurity strategy in Indonesia.